2007
DOI: 10.1097/wnn.0b013e3180335f7d
|View full text |Cite
|
Sign up to set email alerts
|

The Semantic Object Retrieval Test (SORT) in Amnestic Mild Cognitive Impairment

Abstract: The SORT is a specific test of semantic memory, and is a sensitive measure of semantic memory deficits in patients who otherwise meet criteria for amnestic MCI. Using this specific assessment tool, a significant number of MCI patients were found to have semantic memory deficits. As these patients may be early in the course of possible progression toward dementia, the SORT or other tests of semantic memory may provide important diagnostic or prognostic information in patients with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 38 publications
3
34
1
Order By: Relevance
“…Brain regions shown to work in conjunction to perform semantic retrieval exhibited covarying activity only in the deployed control group, and not in the affected groups. These significant differences between clinical groups relative to controls demonstrate the sensitivity of the SORT task in distinguishing clinical populations, similar to what was found in previous studies using the same task (Assaf et al 2005;Kraut et al 2006Kraut et al , 2007. Comparisons of task performance showed both significant differences and trends toward poorer performance when comparing Syndromes 1 and 3 with the deployed control group, and there were no clear differences in specific performance parameters that distinguished between Values followed by asterisk (*) represent a significant correlation (p<.05) between regions the affected veteran groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Brain regions shown to work in conjunction to perform semantic retrieval exhibited covarying activity only in the deployed control group, and not in the affected groups. These significant differences between clinical groups relative to controls demonstrate the sensitivity of the SORT task in distinguishing clinical populations, similar to what was found in previous studies using the same task (Assaf et al 2005;Kraut et al 2006Kraut et al , 2007. Comparisons of task performance showed both significant differences and trends toward poorer performance when comparing Syndromes 1 and 3 with the deployed control group, and there were no clear differences in specific performance parameters that distinguished between Values followed by asterisk (*) represent a significant correlation (p<.05) between regions the affected veteran groups.…”
Section: Discussionsupporting
confidence: 88%
“…For example, increased BOLD signal in early Mild Cognitive Impairment (MCI) is proposed to indicate an increase in effort in an attempt to maintain performance in a dysfunctional system, similar to Syndrome 2. As degenerative changes progress to later MCI and/or early Alzheimer's disease (AD), these findings change to decreased BOLD responses accompanied by impaired task performance (Kraut et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Visual memory tests that have received attention in the literature include Wechsler Memory Scale’s Visual Reproduction [15] and the Rey–Osterrieth Complex Figure Test (RCFT) [2325]. Measures of executive and language functioning that may predict conversion include Trail Making Test B (TMT B) [15,2529], Wechsler Adult Intelligence Test-Revised digit symbol coding [21], Stroop Color Naming [30], Wechsler Memory Scale-Revised digit span [31], semantic fluency [32,33] and the Boston Naming Test (BNT) [34,35]. …”
mentioning
confidence: 99%
“…Moreover, the BNT may possess particular predictive ability due to its assessment of long-term memory. A couple of studies have found that the BNT effectively predicts conversion to AD [35,45]. …”
mentioning
confidence: 99%
“…Conversion rates of 15 to 20% from mild cognitive impairment (MCI) to frank dementia over two years have been reported (Petersen, 2004;Gauthier et al, 2006;Mauri et al, 2012). Neuropathological findings in MCI patients are characterized by significant structural changes in the ventromedial temporal lobe (Markesbery et al, 2006), known to be involved in semantic memory (Davies et al, 2004), which correlate with a subtle clinical semantic deficit (Duong et al, 2006;Kraut et al, 2007;Gardini et al, 2013). Recently the concept of MCI has also been applied to PD and the entity MCI-PD (mild cognitive impairment in Parkinson's disease) has been proposed (Litvan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%